PS01.037: APPLYING THORACIC ENDOVASCULAR AORTIC REPAIR (TEVAR) AND SURGICAL RESECTION WITH RECONSTRUCTION OF ESOPHAGUS IN MANAGING OF AORTA-ESOPHAGEAL FISTULA. (14th September 2018) - Chou, Yi-Pin; Lin, Hsing-Lin
Abstract: Background: Aorta-esophageal fistula (AEF) is very dangerous with high mortality. Treatment is difficult because of hemorrhagic shock in acute stage and infection in sub-acute stage. We develop a method to manage both perforations from aorta and esophagus successfully. Methods: A 56 male patient had fish bone incarcerated in thoracic esophagus. Two months after this accident, intermittent massive hematemesis occurred. The esophagoscopy displayed active bleeding and AEF was diagnosed by computed tomography angiography (CTA). TEVAR is applied immediately and stopped bleeding successfully. Fever with sepsis and mediastinitis was happened after oral intake. The perforated esophagus was removed by wire-stripper through neck and abdomen incisions and reconstructed with gastric tube via retro-sternal route. Results: After subtotal esophagectomy with gastric tube reconstruction, the ventilator is weaned and endotracheal tube was removed. No leakage from anastomosis between cervical esophagus and gastric tube. Patient could swallow regular diet smoothly. No further post-operative complication was happened after follow up two years. Conclusion: TEVAR is the first step in managing AEF in acute stage to prevent hemorrhagic shock. Although esophageal perforation could be managed with esophageal stent, the marginal ulcer with pain and bleeding may cause other side effects. Esophageal stent is also another contra-indication applied in benign disease. Subtotal esophagectomy with wire-stripper and reconstruction with gastric tube could provide definite treatment for this esophageal perforation. Disclosure: All authors have declared no conflicts of interest.